2004
DOI: 10.1177/030089160409000602
|View full text |Cite
|
Sign up to set email alerts
|

Benign Breast Diseases in Breast Cancer Screening Programs in Italy (2000-2001)

Abstract: Detection of BBD occurred frequently in breast screening programs, and prognostic implications should be further investigated. Women should be individually informed at screening, and with greater detail at the moment of the recall for assessment, of the implications of BBD detection and receive the necessary, also psychological, counseling to avoid the possible harm related to breast cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…33 In screening activities, the role of breast lesions at risk of developing cancer needs to be redefined. In accordance with other authors, 33,34 we believe that it is inappropriate to include breast lesions at risk of developing cancer in the overall benign open biopsy rate and that it is time to define a screening performance indicator that audits the detection of these lesions.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…33 In screening activities, the role of breast lesions at risk of developing cancer needs to be redefined. In accordance with other authors, 33,34 we believe that it is inappropriate to include breast lesions at risk of developing cancer in the overall benign open biopsy rate and that it is time to define a screening performance indicator that audits the detection of these lesions.…”
supporting
confidence: 74%
“…Fibroadenoma and fibrocystic disease were the most frequent lesions included in the current and previously published series 31,32,34,52 (Table 6). Previous studies on screening series have demonstrated that greater numbers of 'pure' benign lesions are being excised 31,32 ( Table 5), but the increasing accuracy of preoperative diagnosis after the introduction of needle biopsy probably will lead to a decrease in this number over time.…”
mentioning
confidence: 77%
See 3 more Smart Citations